PETAGANAL (Pelatihan Tari Dan Gamelan Tradisional) Di Panti Asuhan Dharma Jati, Denpasar - Sari Maheswari, Anak Agung Sagung; Kanya Mitha Gunapadmi, Ni Putu; Ari Ananta Paramarta, Pande Made; Lestari Damaiyanti, Ni Putu Ayu; Ni Nyoman, Ni Nyoman (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 21 No 1 (2021)DO - 10.24843/PJIIB.2021.v21.i01.p07, 2021)
Culture has become a national cultural heritage, where culture is not only seen from the physical side as a beauty but more than that is the philosophical values contained in it. Dance and traditional musical instruments must be introduced and taught early. The orphanage children have the right to receive education and training to receive traditional, also they are including the next generation who must preserve education in Indonesia. The method used is by conducting counseling, training, and mentoring techniques. This program lasts for four months with the potential results obtained, namely in the distribution of scientific, social and educational articles through learning by videos.